FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH: INTERNAL CONTROL SYSTEM SEBAGAI VARIABEL MODERASI - Enda Reska Marista Br Tarigan, (2023)
This research is a quantitative study which aims to determine the effect of intergovernmental revenue, budget expenditure, per capita income and the level of dependence on the level of disclosure of LKPD with a moderating variable internal control system. The sample is 468 LKPD from all local or city governments in Indonesia which have been audited by BPK for the 2021 period with purposive sampling. The analysis technique used is path analysis using Smart PLS 3.3.3 software and a significance level of 5%. The results of the study found 1) intergovernmental revenue has an effect on the level of disclosure on LKPD 2) budget expenditure has an effect on the level of disclosure on LKPD 3) per capita income has no effect on the level of LKPD disclosure 4) the level of dependence has an effect on the level of disclosure on LKPD 5) Internal control system cannot moderate the effect of intergovernmental revenue on the level of disclosure of LKPD 6) Internal control system moderates the influence of budget expenditure on the level of disclosure of LKPD 7) Internal control system cannot moderate the effect of per capita income on the level of disclosure of LKPD 8) Internal control system cannot moderate the effect of level of dependence on the level of disclosure of LKPD.